2006
DOI: 10.34194/geusb.v9.4856
|View full text |Cite
|
Sign up to set email alerts
|

Borehole seismic studies of a volcanic succession from the Lopra-1/1A borehole in the Faroe Islands, northern North Atlantic

Abstract: Extruded basalt flows overlying sedimentary sequences present a challenge to hydrocarbon exploration using reflection seismic techniques. The Lopra-1/1A re-entry well on the Faroese island of Suðuroy allowed us to study the seismic characteristics of a thick sequence of basalt flows from well logs and borehole seismic recordings. Data acquired during the deepening operation in 1996 are presented here. The re-entry well found that the seismic event at 2340 m, prognosed from the pre-drill Vertical Seismic Profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 12 publications
5
35
0
Order By: Relevance
“…However, Maresh et al (2006) showed that rough surface effects appear to be small compared to one-dimensional (1D) impedance scattering losses for the basalts penetrated in Well 164/07-1 in the nearby Rockall Trough, suggesting that a good estimate of scattering loss can be calculated with a 1D earth model. VSP-derived Q values of layered basalts have been reported from various igneous provinces (Rutledge and Winkler 1989;Pujol and Smithson 1991;Christie, Gollifer and Cowper 2006;Maresh et al 2006;Shaw et al 2008) with values of Q eff,P in the range of 15-48. The subscripts P and S for Q indicate compressional (P-) and shear (S-) wave measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Maresh et al (2006) showed that rough surface effects appear to be small compared to one-dimensional (1D) impedance scattering losses for the basalts penetrated in Well 164/07-1 in the nearby Rockall Trough, suggesting that a good estimate of scattering loss can be calculated with a 1D earth model. VSP-derived Q values of layered basalts have been reported from various igneous provinces (Rutledge and Winkler 1989;Pujol and Smithson 1991;Christie, Gollifer and Cowper 2006;Maresh et al 2006;Shaw et al 2008) with values of Q eff,P in the range of 15-48. The subscripts P and S for Q indicate compressional (P-) and shear (S-) wave measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The subscripts P and S for Q indicate compressional (P-) and shear (S-) wave measurements. In addition to their Q eff,P estimates, Rutledge and Winkler (1989), Christie et al (2006) and Maresh et al (2006) also calculated Q scat,P by elastic modelling, using a point source in a plane-layered medium characterized by well-log velocities and densities. They found that the dominant attenuation mechanism was caused by impedance scattering because their Q scat,P matched Q eff,P , within experimental error.…”
Section: Introductionmentioning
confidence: 99%
“…a decrease in the acoustic impedance with depth (Christie et al, 2006). Furthermore, approximately 700 m of lower FIBG strata has been estimated to have been eroded at this location (Andersen et al, 2002;Jørgensen, 2006) (Figure 7a), which implies an original total thickness of at least 4.2 km of lower FIBG.…”
Section: Lower Fibg (Lopra and Beinisvørð Formations)mentioning
confidence: 94%
“…At present, the only regional seismic horizon identified within the FIBG is the A-horizon, an erosional and eruption hiatus which separates the Beinisvørð and Malinstindur formations (Petersen, Brown, & Andersen, 2015) ( Figure 2). The base of the basalt lava pile can also be mapped on seismic-reflection profiles locally in the Faroese sector of the Faroe-Shetland Basin (Ellefsen, Boldreel, & Larsen, 2010) and is observed in the Lopra-1 well that terminated in hyaloclastic rocks of the Lopra Formation (Boldreel, 2006;Christie, Gollifer, & Cowper, 2006). Although refraction-seismic interpretations suggest that sedimentary rocks might be present below the FIBG in the western part of the Faroe-Shetland Basin and beneath the Faroe Platform, including Lower Paleocene rocks (Kiørboe & Petersen, 1995;Ólavsdóttir et al, 2017;Pálmason, 1965;Raum et al, 2005;Richardson, Smallwood, White, Snyder, & Maguire, 1998;Richardson, White, England, & Fruehn, 1999;Smallwood & Maresh, 2002;Smallwood & White, 2002;White et al, 2008), their correlation with the rock record in the eastern part of the Faroe-Shetland Basin remains ambiguous.…”
Section: Faroe Islands Basalt Groupmentioning
confidence: 99%
See 1 more Smart Citation